PRELIMINARY EVALUATION OF THE EFFECTIVENESS OF HIFU-THERAPY IN PATIENTS WITH PANCREATIC CANCER - L. B. Bolotina; L. I. Moskvicheva; A. L. Kornietskaya; D. V. Sidorov; N. A. Grishin; M. V. Lozhkin; A. D. Kaprin (Сибирский онкологический журнал)
Purpose: to conduct a preliminary analysis of the safety and effectiveness of hifu-therapy with a lowenergy hifu-2001 device (shenzhen Huikang Medical apparatus Co., ltd) performed concurrently with chemotherapy in pancreatic cancer patients who are not suitable for surgery or chemoradiotherapy.Material and Method. The study included 24 pancreatic cancer patients who were treated at the Hertsen Moscow Oncology Research institute in the period from 2016 to 2019. There were 17 (71 %) women and 7 (29 %) men. The percentage of patients in the elderly group was 79 %. Stage iia pancreatic cancer was diagnosed in 3 (12.5 %) patients, stage ii in 5 (21 %) patients, stage iii in 9 (37.5 %) patients, and stage iv in 7 (29 %) patients. All patients received combination therapy, including systemic chemotherapy and hifu-therapy. Results. The most frequent adverse events of treatment were skin burns (n=6), with third-degree burns occurring in 2 (8.3 %) patients. Local sclerosis of subcutaneous adipose tissue was observed in 4 (17 %) patients; development of asymptomatic pancreatic pseudocysts in the area of hifu exposure was observed in 1 (4 %) patient. Pain control was achieved in 17 (85 %) patients, and local tumor control was achieved in 19 (79.2 %) patients. The follow-up time ranged from 5 to 30 months with a median time of 14.5 months. The median total life expectancy of patients was 16 months, and the median time to progression was 9 months. The overall 6-month survival rate was 100 %. The 1- and 1.5-year survival rates were 75.0 % and 41.7 %, respectively. The 2-year survival rate was 17.2 %. The 6-month and 1-year disease-free survival rates were 62.5 % and 12.5 %, respectively. Conclusion. The short- and long-term outcomes were consistent with those described in other studies, which indicated that a combination of systemic drug therapy and hifu-therapy is an appropriate approach for the treatment of patients with pancreatic cancer.